Trudności w diagnostyce i leczeniu zdysocjowanego odchylenia pionowego (DVD). Część I. - Loba, Piotr; Broniarczyk-Loba, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Dissociated vertical deviation (DVD) is a poorly understood eye motility disorder of unexplained etiology. It occurs as a common hyperdeviation present in most cases of congenital esotropia, but also appears in patients with normal binocular vision and exotropia. DVD is a bilateral condition, often with distinct asymmetry. Its clinical characteristics includes elevation, extorsion and abduction of the nonfixating eye, with fixating eye incyclotorting concomitantly. Commonly it is associated with a compensatory head tilt. Main problem of DVD diagnostics of DVD is quantification of its magnitude due to large variability of various measurements during one eye examination, and usually one fails trying to obtain reproducible measurements in one patient. Therefore, establishing of a proper treatment plan is often unfeasible. Differential diagnosis is occasionally difficult in individuals with inferior and superior oblique overaction with or without co-existing DVD. Primary goal of DVD management is to improve patients’physical looks so that the upward turning of the eye is hardly noticeable. Both conservative as well as surgical treatment should be considered. Planning and performing the effective surgery is extremely difficult in DVD; and various surgical approaches to DVD are used worldwide.